Phosphine-Free Palladium-Catalyzed Direct C-3 Arylation of 2-Phenylimidazo[1,2-a]pyridine Using Silver(I) Carboxylate - Sridevi Kona; Rama Suresh Ravi; Manab Chakravarty; Venkata N. R. Chava (Journal of Chemistry)
Phosphine-free palladium-catalyzed direct arylation of 2-phenyl-imidazo[1,2-a]pyridine has been developed with the concept of using silver(I) carboxylate. This protocol efficiently catalyzes the C-H arylation of 2-phenyl-imidazo[1,2-a]pyridine with aryl iodides to afford the corresponding 2-phenyl-3-aryl-imidazo[1,2-a]pyridines in moderate to-good yields.